Farmer’s Perception and Awareness about Tree Insurance in Namakkal, Tamil Nadu - R, Deepak kumar (Indian Journal of Hill Farming, 2018)
Agroforestry is one of the emerging field in agriculture due to efficient utilization of resources, low labour intensity and low maintenance but the sametime better yield and income. More than seventy percent of farmers having the 6-10 years experiences in the tree cultivation. Cereals and millets are the predominant crops in Namakkal taluks whereas pulses and oil seeds are predominant crops in Tiruchengode taluks. Around fifty percent of tree farmers in the sample taluks are facing weather as major risks followed by pests and human interference. These were not only reduce the yield but also loss of huge investment which may limit the scope of expansion of tree cultivation. In these context, tree insurance as a risk management tool by providing financial support to tree farmers. The present study focus on farmer’s perception and awareness of tree insurance in Namakkal region in Tamil Nadu which experiences the prolonged dry spell.